2006
DOI: 10.1253/circj.70.222
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Men and Women in Terms of Clinical Features of ST-Segment Elevation Acute Myocardial Infarction

Abstract: any studies of sex-related differences in the shortand long-term outcomes of acute myocardial infarction (AMI) have concluded that mortality is higher among women than men. [1][2][3][4][5][6][7][8][9][10] The reason for poorer outcomes in women remains unclear. The higher mortality among women may be partially explained by the fact that women were older than men and had higher rates of unfavorable prognostic factors in previous studies. After the adjustment for these factors, however, several studies continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 30 publications
2
51
0
8
Order By: Relevance
“…In the current study analyzing a recent AMI cohort treated by primary PCI, in-hospital mortality was higher among the women than the men, which is in accordance with a previous study showing higher in-hospital mortality despite lower peak creatinine phosphokinase levels in Japanese female patients with ST-elevation MI (STEMI). 26 Thus, in-hospital mortality was still higher among the women in a more recent cohort with more frequent use of cardioprotective agents and higher success rate of PCI. [26][27][28] Contrary to this, including the current study, a population-based study of 201,114 people in Scotland showed that the 30-day case fatality rate was lower in women than in men, when deaths from AMI that occur without hospital admission were taken into consideration.…”
Section: Characteristics Related To MI and Revascularization Procedurmentioning
confidence: 96%
See 1 more Smart Citation
“…In the current study analyzing a recent AMI cohort treated by primary PCI, in-hospital mortality was higher among the women than the men, which is in accordance with a previous study showing higher in-hospital mortality despite lower peak creatinine phosphokinase levels in Japanese female patients with ST-elevation MI (STEMI). 26 Thus, in-hospital mortality was still higher among the women in a more recent cohort with more frequent use of cardioprotective agents and higher success rate of PCI. [26][27][28] Contrary to this, including the current study, a population-based study of 201,114 people in Scotland showed that the 30-day case fatality rate was lower in women than in men, when deaths from AMI that occur without hospital admission were taken into consideration.…”
Section: Characteristics Related To MI and Revascularization Procedurmentioning
confidence: 96%
“…26 Thus, in-hospital mortality was still higher among the women in a more recent cohort with more frequent use of cardioprotective agents and higher success rate of PCI. [26][27][28] Contrary to this, including the current study, a population-based study of 201,114 people in Scotland showed that the 30-day case fatality rate was lower in women than in men, when deaths from AMI that occur without hospital admission were taken into consideration. 10 Because the current study could not assess prehospital information, our results should be carefully interpreted.…”
Section: Characteristics Related To MI and Revascularization Procedurmentioning
confidence: 96%
“…and these conditions have been associated with MI without pain. 29,32,33 For patients who did not report chest pain, there were no sex differences in the symptoms reported, possibly due to insufficient statistical power due to small numbers. The most common non-chest pain symptoms for both men and women were shortness of breath, a fall, or collapse, syncope or unconsciousness.…”
Section: Sex Differences In Chest Painmentioning
confidence: 99%
“…또한, AMI의 발생 시 환자가 호소하는 증상 가운데 비전형적인 증상이 남성보다 여성에서 훨씬 많다고 보고되었 다 [11]. 즉, 남성은 AMI의 임상증상으로 흉통이나 발한을 보 고하는 반면, 여성은 등, 턱, 목에 오는 통증, 구역과 구토, 호흡 곤란, 피로, 식욕부진 등을 더 경험한다고 하였다 [11,12] …”
unclassified